2022
DOI: 10.1002/rth2.12671
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiovascular risk factors and venous thromboembolism in the elderly

Abstract: Background The preponderance of the evidence supports no association between traditional cardiovascular risk factors and venous thromboembolism (VTE), other than obesity. There are limited data in older people. Objectives To investigate whether cardiovascular risk factors (body mass index, smoking, alcohol intake, hypertension, and diabetes) are associated with the risk of VTE in elderly and to assess the combined effect between cardiovascular risk factors and genetic risk factors for VTE (factor V Leiden/prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
3
1
Order By: Relevance
“…No significant impact of tobacco smoking on VTE risk was found by univariate MR analysis, which was consistent with the conclusions reached by multivariable MR analysis after controlling for potential effects. In contrast with many observational studies that have concluded that tobacco smoking (current or past) increased the risk of VTE, 7 8 9 10 the findings of the present study contradict this and instead support the conclusion of Blondon et al 12 13 14 46 that tobacco smoking is not associated with the risk of VTE.…”
Section: Discussioncontrasting
confidence: 99%
“…No significant impact of tobacco smoking on VTE risk was found by univariate MR analysis, which was consistent with the conclusions reached by multivariable MR analysis after controlling for potential effects. In contrast with many observational studies that have concluded that tobacco smoking (current or past) increased the risk of VTE, 7 8 9 10 the findings of the present study contradict this and instead support the conclusion of Blondon et al 12 13 14 46 that tobacco smoking is not associated with the risk of VTE.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the relationship between hypertension and VTE risk appears complex and requires further investigation to understand the roles of the involved variables. 34 In this study, the Wells' score obtained from the study population had a value of 15, with a percentage of 42.8% for a score of 1 and 57.2% for a score of 2. Therefore, the probability of DVT based on the Wells' score falls into the moderate range for all 35 (100%) patients.…”
Section: Resultsmentioning
confidence: 56%
“… 18 Mendelian randomization analyses 19 , 26 showed inverse associations of SBP and VTE. The Age and Thrombosis, Acquired and Genetic risk factors in the elderly (AT‐AGE) study 20 and the second Nord‐Trøndelag Health Study (HUNT 2) 25 found SBP and DBP were inversely correlated to VTE among elderly (age ≥70 years) and adult residents, respectively.…”
Section: Discussionmentioning
confidence: 99%